Implementing an Autonomy-Supportive Intervention to Develop Mental Toughness in Adolescent Rowers - Mahoney, J.; Ntoumanis, Nikos; Gucciardi, Daniel; Mallett, C.; Stebbings, J. (2016)
It was hypothesized that autonomy-supportive coaching behaviors, psychological needs satisfaction, and mental toughness would increase, and controlling coaching behaviors and psychological needs thwarting would decrease following a coach-directed autonomy-supportive intervention. Data related to these hypotheses were collected with coaches (N = 18) and adolescent rowers (N = 61) prior to and following an 8-week intervention, and 8 weeks following the intervention. Coaches were interviewed following data collection about their involvement in the intervention. Results did not support the hypotheses. Qualitative analyses revealed that autonomy-supportive behaviors might not have been adopted due to contextual pressures on the coaches.